Characterization of VopJ by modelling, docking and molecular dynamics simulation with reference to its role in infection of enteropathogen Vibrio parahaemolyticus. Issue 5 (8th March 2021) - Raval, Ishan H.; Labala, Rajendra K.; Raval, Krishna H.; Chatterjee, Shruti; Haldar, Soumya
Abstract: Vibrio parahaemolyticus is a renowned enteropathogen known for infecting humans. The infection usually involves various genes which help bacterium bypass the immune system of the host. Type III secretion system (T3SS) is an essential factor for the infection. The present study introduces the probable structure of VopJ, a T3SS effector of V. parahaemolyticus . The vopJ gene was amplified and sequenced from V. parahaemolyticus. The model generated through homology modelling showed a Z score of around 2.5, which fits quite near in the standard model available in the databases. The model has only a couple of outlier amino acids, which indicate a good fit of the model. Docking studies with small molecules like Acetyl-CoA, Inositol hexakisphosphate, GTP, and AMP have shown negative Δ G  − 10.49, −52.80, −8.36 and −9.02, respectively, which indicates spontaneous binding. The molecular simulation studies have also supported the binding with a low RMSD value of less than 0.5 nm. The RMSF values obtained using the modelling were also quite low (>0.35 nm), which indicates the consistency achieved using the docking studies. These small molecules are very crucial in the MAPK pathways, which is essential for the immune response from the host cell. This effector can thus have an ability to highjack the immune system and help the bacterium in the potent infection. Up to our understanding, this is the first report which describes the in-silico model to understand the mode of infection of T3SS in enteropathogen V. parahaemolyticus . Communicated by Ramaswamy H. Sarma